Cárie dentária em pacientes de transplante de células tronco hematopoiéticas, fígado e rim: aspectos clínicos, epidemiológicos e salivares - Carla de Souza Oliveira (2020)
The aim of this study was evaluate the experience of tooth decay and associated factors in hematopoietic stem cell, liver and kidney transplant patients. The impact of oral health on the quality of life of these individuals and its association with the experience of caries and salivary flow were also evaluated. A controlled analytical cross-sectional study with 40 transplant individuals and 40 controls not indicated for transplantation, matched for age and sex, attended at the UFMG School of Dentistry (Brazil) was conducted. Sociodemographic and economic data, medications in use and post-transplant time were collected. The caries experience was evaluated using the CPOS and COR (surface) indexes. The impact of oral health on quality of life was measured using the Oral Health Impact Profile (OHIP-14). Saliva was collected to obtain flow, pH, chemical composition and buffering capacity. The intake of free sugars was evaluated by the 24-hour recall. The regression analysis showed that the increase of an individual living in the patient's home increases the chances of having a high caries experience (OR =1.35; 95% CI 1.02-1.79). The increase of one point in the salivary flow decreased the chances of high experience of dental caries (OR=0.14; 95% CI 0.03-0.72). As for the impact of oral health on quality of life, individuals in conditions of liver transplantation had significantly higher median values (4.0 [0-7.0]) compared to those of kidney transplantation (0.5 [0- 5]) (p = 0.043), for the psychological discomfort domain. The medians of the number of surfaces lost were significantly higher in the liver transplant subjects (45.0 [0-81.0]), compared to the kidney (12.0 [0-65.0]) (p = 0.045). The kidney transplant individuals (32.5 [1.0-58.0]) had significantly higher number of restored surfaces, compared to the liver (13.0 [0-32.0]) (p = 0.049). The age group between 56 and 61 years old (13.0 [7.0-25.0]) presented higher OHIP-14 values, compared to the age group from 25 to 40 years old (4.5 [0-29.0]) (p=0.013). The OHIP-14 values showed a significant moderate positive correlation, with the number of missing dental surfaces (ρ = 0.433; p = 0.005). There was no correlation between the OHIP-14 value and the salivary flow. It was concluded that the increase in salivary flow decreased the chances of the individual having a high experience of caries. The increase in the number of individuals living in the home increased the chances of high caries experience. Individuals with liver transplantation had greater psychological discomfort and a greater number of missing dental surfaces, compared to those of kidney transplantation. The greater tooth loss was correlated with a worse impact of oral health on the quality of life of transplant individuals. Individuals over 56 years of age demonstrated a greater impact on quality of life related to oral health.